Capung (Ordo: Odonata) di Kawasan Reklamasi Bekas Tambang Timah, Belinyu, Bangka - Alita, Alita; Nurtjahya, Eddy; Sutrisno, Hari (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
Dragonflies are bioindicator insects that are known to be sensitive to the environment and their existence is influenced by habitat conditions. The potential of dragonflies as a bioindicator for the success of reclamation efforts for former tin mining on Bangka Island needs to be studied. This research aims to record the diversity of dragonflies and damselflies in reclaimed land covering an area of ±15.25 ha and aged ±16 years as one component to enrich the criteria for assessing the success of revegetation of ex-tin mining land. This research was conducted in the rainy season, January-March 2023. For three weeks, Schnabel's visual encounter survey (VES) and capture-mark-release-recapture (CMRR) methods were chosen to observe five transect lines, respectively non-revegetation areas, horticultural and fruit revegetation areas, oil palm revegetation areas, kolong with tilapia fish, and kolong with human activities. This research recorded 19 species of dragonflies and 6 species of damselflies, or around 6.5% of the dragonflies and 2.0% of the damselfly species on the island of Sumatra. The most dominant species are Neurothemis fluctuans and Ceriagrion cerinorubellum. The number of species and number of individual dragonflies is thought to be related to the age of reclamation, and has the potential to be an indicator of the success of ex-tin mining reclamation land. Keywords:“Area Type”; “Bangka”; “Bioindicator”; “Dragonfly”; “Ex-Mined Land Reclamation”